2014
DOI: 10.1186/s12866-014-0307-2
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Mycobacterium tuberculosis and drug resistance in different provinces of Papua New Guinea

Abstract: BackgroundPapua New Guinea (PNG) is a high tuberculosis (TB) burden country of the WHO Western Pacific Region, but so far research on drug resistance (DR) and genotypes of Mycobacterium tuberculosis (M. tuberculosis) was only conducted in few provinces in the country. The aim of the present study was to obtain baseline data on the level of drug resistance and the genotypic diversity of circulating M. tuberculosis in additional provinces and to investigate the differences between three selected sites across PNG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…they showed no homoplasy. We selected a subset of these sublineage-specific SNPs and used these to screen a global collection of 3,366 Lineage 4 clinical isolates from 100 countries using various genotyping platforms3035. First, we developed a novel sublineage-specific multiplexed SNP-typing assay using the Luminex platform as previously reported36, and used that method to screen 2,001 isolates (Supplementary Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…they showed no homoplasy. We selected a subset of these sublineage-specific SNPs and used these to screen a global collection of 3,366 Lineage 4 clinical isolates from 100 countries using various genotyping platforms3035. First, we developed a novel sublineage-specific multiplexed SNP-typing assay using the Luminex platform as previously reported36, and used that method to screen 2,001 isolates (Supplementary Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…These represented the largest collection of Lineage 4 whole-genome sequences available at that time. For the SNP-screening of clinical isolates for sublineage-classification, we used a retrospective global collection of 3,366 MTBC Lineage 4 isolates from 100 countries (Supplementary Table 5)15,3035. All isolates had previously been identified as MTBC Lineage 4 by SNP-typing, genomic deletion analysis or spoligotyping.…”
Section: Methodsmentioning
confidence: 99%
“…A study from Kikori in Gulf Province of PNG reported 9% (3 of 32 TB cases) of rifampicin resistant cases among TB patients (Cross, Coles et al .) [ 8 ] and another one reported MDR-TB in 2.8% of all cases tested in three sites (Ley, Harino et al) [ 9 ]. These studies were small in nature and not designed to obtain population-representative data, therefore a large representative survey was needed to determine the real burden of anti-TB drug resistance in PNG.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings indicate that the large number of MDR TB cases detected on Daru Island in the Western Province of Papua New Guinea is driven by the transmission of a highly drug resistant cluster of modern Beijing lineage strain. Studies from other parts of Papua New Guinea demonstrated a dominance of Euro-American lineage strains, (20, 21) although the contribution of Beijing lineage strains may have been underestimated in these limited surveys. We cannot comment on the geographic spread of this outbreak cluster, but phylogenetic analysis combined with detailed molecular dating suggests that it has been in local circulation since the 1940s and first acquired drug resistance mutations in the 1960s.…”
Section: Discussionmentioning
confidence: 80%